Semi-supervised training to improve player and ball detection in soccer - Vandeghen, R.; Cioppa, A.; Van Droogenbroeck, M. (IEEE/CVF Conference on Computer Vision and Pattern Recognition, 2022)
Accurate player and ball detection has become increasingly important in recent years for sport analytics. As most state-of-the-art methods rely on training deep learning net-works in a supervised fashion, they require huge amounts of annotated data, which are rarely available. In this pa-per, we present a novel generic semi-supervised method to train a network based on a labeled image dataset by lever-aging a large unlabeled dataset of soccer broadcast videos. More precisely, we design a teacher-student approach in which the teacher produces surrogate annotations on the unlabeled data to be used later for training a student which has the same architecture as the teacher. Furthermore, we introduce three training loss parametrizations that allow the student to doubt the predictions of the teacher during training depending on the proposal confidence score. We show that including unlabeled data in the training process allows to substantially improve the performances of the detection network trained only on the labeled data. Finally, we provide a thorough performance study including different proportions of labeled and unlabeled data, and establish the first benchmark on the new SoccerNet-v3 detection task, with an mAP of 52.3%. Our code is available at [https://github.com/rvandeghen/SST].